PENGARUH KONSENTRASI AGAR BATANG TERHADAP KARAKTERISTIK FISIKOKIMIA DAN ORGANOLEPTIK SELAI MURBEI HITAM (Morus nigra L.) LEMBARAN - Sunyoto, Ronny Kusuma; Suseno, Thomas Indarto Putut; Utomo, Adrianus Rulianto (Jurnal Teknologi Pangan dan Gizi, 2017)
Mulberry jam sheet is modified product from jam with the addition of gelling agent such as sugar as sweetening and preservative agent also agar bar and carrageenan as gelling agent. Mulberry jam sheet was more practice in form and size which has been adapted with sliced form of bread compared with normal jam. Production of mulberry jam sheet needs addition of gelling agent to form solid texture. The addition of agar bar can affects mulberry jam sheet’s characteristics, therefore it was necessary to study the effect of the concentration of agar bar. The methodology of this research was a randomized block design (RBD) with one factor, that was the concentration of agar bar (P), which consists of six levels 0.6% (P1); 0.8% (P2); 1.0% (P3); 1.2% (P4); 1.4% (P5); dan 1.6% (P6) of mulberry puree used. Repetition of the experiments are carried out four times. Difference concentration of addition agar bar affect moisture content, texture (hardness, adhesiveness, and cohesiveness), and texture organoleptic parameter. Increasing concentration of agar bar caused a decreased of moisture content, syneresis level, and lightness also increased of hardness, adhesiveness, and cohesiveness. Increasing agar bar concentration was not affect antioxidant activity also taste and color organoleptic. The color of mulberry jam sheet was purple-black. Best treatment of mulberry jam sheet was addition of 1% agar bar which had moisture content 30.48%, hardness 845.379 g, adhesiveness -914.791 g.s, cohesiveness 0,917, also sensory score taste 5.0160, color 4.9721, and texture 5.5966 with score 1-7 as standart.